2021
DOI: 10.1158/1078-0432.ccr-20-0121
|View full text |Cite
|
Sign up to set email alerts
|

Optimized EGFR Blockade Strategies in EGFR Addicted Gastroesophageal Adenocarcinomas

Abstract: Purpose: Gastric and gastroesophageal adenocarcinomas (GEA) represent the third leading cause of cancer mortality worldwide. Despite significant therapeutic improvement, the outcome of patients with advanced GEA is poor. Randomized clinical trials failed to show a significant survival benefit in molecularly unselected patients with advanced GEA treated with anti-EGFR agents. Experimental Design: We performed analyses on 4 cohorts: IRCC (570 patients), FMI (9397 patients), COG (214 patients) and INT (206 patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Nevertheless, novel translational research and experimental preclinical data showed a positive correlation between cetuximab response and high EGFR expression/ amplification, which occur in 3-4% of all cases, and let investigator rethink on how to optimize the treatment strategy. In fact, a recent study conducted in PDX xenopatien models has confirmed that EGFR inhibitors may be active in EGFR-addicted gastric adenocarcinoma with EGFR copynumber gain 87 and may serve as springboard for future research to identify potentially actionable targets and resistance mechanisms.…”
Section: Egfr Inhibitorsmentioning
confidence: 99%
“…Nevertheless, novel translational research and experimental preclinical data showed a positive correlation between cetuximab response and high EGFR expression/ amplification, which occur in 3-4% of all cases, and let investigator rethink on how to optimize the treatment strategy. In fact, a recent study conducted in PDX xenopatien models has confirmed that EGFR inhibitors may be active in EGFR-addicted gastric adenocarcinoma with EGFR copynumber gain 87 and may serve as springboard for future research to identify potentially actionable targets and resistance mechanisms.…”
Section: Egfr Inhibitorsmentioning
confidence: 99%
“…EGFR amplification predicts aggressive biological behavior and poor prognosis. Preclinical trials performed on PDX models with EGFR -amplified gastroesophageal adenocarcinoma revealed that the cetuximab and lapatinib/erlotinib combination still results in a deep and durable response ( 58 ). Similarly, in a study evaluating the biliary tract cancer cell line HuCCT1 ( in vitro cell proliferation inhibition and apoptosis promotion) and pancreatic cancer cell line Panc430 xenografts, tumor growth in vivo was significantly decreased with combined therapy (gefitinib/erlotinib and cetuximab) ( 44 ).…”
Section: “Sandwich” Strategy For Other Tumorsmentioning
confidence: 99%
“…Unfortunately, phase II trials have shown that these therapies have limited efficacy [22,23]. Recently, Maron et al and Corso et al identified a subpopulation of GC patients presenting a high level of EGFR amplification, which is responsive to anti-EGFR drugs [24,25]. They also identified mechanisms of resistance to EGFR-targeted drugs, such as TKR activation, KRAS mutation/amplification, and TSC2 inactivation [25].…”
Section: Anti-her1mentioning
confidence: 99%
“…More recently, a preclinical trial on PDXs allowed a TSC2 mutation leading to increased resistance to EGFR inhibition to be identified. The pharmacological inhibition of TSC2 was positively tested with everolimus, which was able to overcome the resistance and to reestablish the sensitivity to EGFR inhibition [25].…”
Section: Preclinical Trialsmentioning
confidence: 99%